2013
DOI: 10.5030/jcigsjournal.28.93
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Type of Leachate on Self-Healing Capacity of Geosynthetic Clay Liner

Abstract: The effect of type of leachate (liquid) on self-healing capacity of the geosynthetic clay liners (GCLs) has been investigated by laboratory leakage rate tests. Four types of liquids, namely, tap water, 10 g/l NaCl solution, 100 ml/l ethanol solution and 11.1 g/l CaCl 2 solution were used. The test results indicate that the types of liquid have a significant effect on self-healing capacity of GCLs through the influence on the amount of hydration induced expansion of the bentonite inside GCLs. Free swelling inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Then, the key issue is how to predict the values of m b , w and t. Based on the laboratory test results reported by Sari and Chai (2013) and Chai et al (2013), the main factors influencing these three quantities are (1) type of liquid; (2) overburden pressure (p 0 ); and (3) the size of a damage hole. Further it has been shown that the effect of type of liquid can be quantified by liquid limit (w l ) and/ or free swelling index (FSI) of the bentonite with a corresponding liquid.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the key issue is how to predict the values of m b , w and t. Based on the laboratory test results reported by Sari and Chai (2013) and Chai et al (2013), the main factors influencing these three quantities are (1) type of liquid; (2) overburden pressure (p 0 ); and (3) the size of a damage hole. Further it has been shown that the effect of type of liquid can be quantified by liquid limit (w l ) and/ or free swelling index (FSI) of the bentonite with a corresponding liquid.…”
Section: Methodsmentioning
confidence: 99%
“…Sodium bentonite as the core material of GCLs which has low hydraulic conductivity [3] and excellent selfhealing ability with water [4]. However, with cationic solution, the permeability of sodium bentonite increases [5,6] and the self-healing ability decreases [7]. under a higher concentration of cation solution environment, GCLs cannot effectively act as a barrier.…”
Section: Introductionmentioning
confidence: 99%
“…The steady flow rate of the intact sample of GCL is also indicated in the figures.For the sample with a damage hole, the values of Q reduced with elapse time and it is considered due to the self-healing of the GCL specimen. At the steady state, the value of Q increases with increasing of size of damage hole for a given damage shape.From the flow rate, the permittivity (hole) of the damage hole can be calculated by Equation(1)…”
mentioning
confidence: 99%